SOCIO-ECONOMIC IMPACTS OF WATER SCARCITY IN DAR ES SALAAM, TANZANIA - Mwakalila, Shadrack (Tanzania Journal of Engineering and Technology, 2018)
Drought and the resulting low water levels in rivers exacerbate water scarcity conditions in Dar es Salaam city. The result is frequent water rationing in areas served with piped water, sometimes for days or weeks, and low water pressure, which leads residents to resort to other less safe and sometimes more expensive water sources. The frequent and current response to the inadequate piped water supply in Dar es Salaam has been the use of groundwater resources. There are both public and private bore-holes and wells drilling companies in Dar es Salaam.. This paper therefore, presents some socio-economic impacts of water scarcity in Dar es Salaam city. The methodology employed in field data and information collection includes interviews, questionnaire, focus group discussions and participatory observation. This is data triangulation, an essential technique for improving the reliability of data and information. The study reveals that the participation of local community (including water vendors and private business entrepreneurs) in water delivery systems through drilling bore-holes and shallow wells has improved water supplies in the study areas. However, the study has revealed some problems related to water scarcity in Dar es Salaam. These include high prices for water, poor sanitation and hygiene, unsafe and unclean water and inconvenient payment systems. Poor sanitation is related to stagnant water around the bore-holes and shallow wells. It is noted that unsafe water is mainly a problem for those obtaining water from water vendors and/or hire young men to collect water for household uses. However, the study concludes that individual ' s participation in water delivery systems in Dar es Salaam City has positively improved the life standards of the local people, particularly the poor.